2019
DOI: 10.21608/jesr.2019.56095
|View full text |Cite
|
Sign up to set email alerts
|

A New Way to Eliminate the Root Rot Fungi in Green Fodder Under the Hydroponic Conditions

Abstract: This study was done to indicate the activity of secondary metabolites of cyanophyta algal extracts for Anabaena Azolla which live in Azolla plant in Egypt and to study the effective of secondary metabolites in An.Azolla extracts (cold water and methanol extracts) to inhibition species of fungi (Fusarium oxysporum, penicillium expansum, Aspergillus niger and candida albicans) also used of HPLC analysis to detected some of active secondary metabolites was done only for methanol extracts also to preliminary state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…possesses the highest antifungal and antibacterial activity against Staphylococcus aureus and Candida albicans. In addition, this outcome aligns with Alrefaey et al (2019) who reported that the methanol extract of Anabaena azolla exhibits the highest antifungal activity against Fusarium oxysporum, Penicillium expansum, Aspergillus niger and Candida albicans. Desertifilum tharense methanol extract, which exhibited the highest antifungal activity against F. oxysporum f. sp.…”
Section: Discussionsupporting
confidence: 89%
“…possesses the highest antifungal and antibacterial activity against Staphylococcus aureus and Candida albicans. In addition, this outcome aligns with Alrefaey et al (2019) who reported that the methanol extract of Anabaena azolla exhibits the highest antifungal activity against Fusarium oxysporum, Penicillium expansum, Aspergillus niger and Candida albicans. Desertifilum tharense methanol extract, which exhibited the highest antifungal activity against F. oxysporum f. sp.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the temperature in the growth chamber must be fully adjusted and automatically controlled, and it must be ensured that the temperature sensor and humidity sensor in the growth chamber are working. In addition, according to Alrefaey 2019 [13], it is possible to improve the hydroponic barley feed and get rid of the root rot fungi by adding Azolla.…”
Section: Introductionmentioning
confidence: 99%